PENGARUH STRATEGI PEMBELAJARAN DAN STATUS SOSIAL EKONOMI ORANG TUA TERHADAP KREATIVITAS ANAK - RAMADHANI, ARIYANI (JURNAL PENDIDIKAN ANAK USIA DINI, 2012)
The objectives of this research are; to find out about the influence of instructional strategies which are inquiry instructional strategy and expository instructional strategy on the early childhood creativity, to find out about the interaction influence between instructional strategies and parents socio economic status towards children creativity, and to find out about the influences of inquiry and expository instructional strategy with different parents socio economic status on children creativity.The results obtained are as follows: 1) there are significant effects of instructional strategies that are given to the creative abilities of children, 2) there are significant interaction effect between instructional strategies and parents socio economic status toward children creativity, 3) children with higher socio economic parents status, would have more significant creativity in inquiry instructional strategy rather than expository instructional strategy.Keywords: instructional strategy, parents socio economic status, creativity